The Efficacy of fractional CO2 laser in management of surgical wound scars - suhan, Abbas M; Darweesh, Maha (AL-Kindy College Medical Journal, 2014)
Background: Atrophic postoperative and traumatic scarring are common cosmetic problems for patients. Combining CO2 laser ablation with a fractional photothermolysis system in a treatment known as ablative fractional resurfacing fulfilling the new demands for a lesser risk of side effects and minimal or no downtime.Objective: To assess the safety and efficacy of ablation fractional CO2 laser treatments for surgical scarring .methods: Twenty one patient ( 14 women, and 7 men ) with various skin types , I to IV , aged 3 to 48 years , presents with 24 scars between June and December 2012 , four patients excluded from study because they are not continued in follow up , the remaining 17 patient completed all 3 treatments & 6 months follow up.Results: Adverse effects of treatment were mild to moderate , and no scarring or delayed onset hypopigmentation was observed, For all patients demonstrated improvements in skin texture and reduction of pain and discomfort and improvement of tenderness and hardness of the scar which become more soft and mature .Conclusions: The ablation CO2 laser treatment represent safe , effective treatment modality for improving scar quality , texture, maturation and appearance.Keywords: Ablative fractional lasers, CO2 lasers, traumatic scars, atrophic scars